EFEKTIVITAS PENEGAKAN HUKUM ADMINISTRASI TERHADAP PELANGGARAN IZIN USAHA PENGELOLAAN DI BIDANG PETERNAKAN ( Studi Di Kecamatan Banyakan Kabupaten Kediri ) - Rudiana, Rudiana; Nurbaedah, Nurbaedah (MIZAN, Jurnal Ilmu Hukum, 2024)
The purpose of this study was to obtain a general description of the effectiveness of administrative law enforcement against violations of management business permits in the livestock sector in order to improve the quality of public services at the Licensing Office of Kediri Regency. To answer the above objectives, the method in this study refers to the type of evaluation research that examines the effectiveness of administrative law enforcement against violations of management business licenses in the livestock sector at the Licensing Service of Kediri Regency with technical data collection using in-depth interviews and observations. While the informants in this study were the Head of the Kediri Regency Licensing Service, the Head of the Field, the Head of the Section, and the Staff. To analyze the data using qualitative analysis techniques with interactive analysis models, namely analysis that moves in three components, namely: data reduction, data analysis, drawing conclusions and verification. Based on the research findings, conclusions can be drawn. The formalization aspect shows that licensing regulations often experience changes in accordance with developments in social and economic dynamics of society and not all types of permits are made in the form of Regional Regulations (Perda). The centralization aspect is good, as evidenced by the existence of an intense coordination system every week to address and evaluate issues related to permits that are being processed. In addition, there is also a control sheet (routing slip) which is a control tool from the agency on staff performance related to congestion or delays in the licensing process. Aspects of specialization, in terms of quantity and quality of human resources is very lacking. However, to overcome these problems, the Licensing Service is conducting capacity building with in-house training and staff training. With the effectiveness of administrative law enforcement against violations of management business permits in the livestock sector, the quality of service to farmers has improved with the results of customer assessments based on the Breeder Satisfaction Index (IKP) and being in the good category. Therefore, the suggestions and recommendations in this study are: First, for licensing regulations in the Licensing Service, all types of permits should be regulated/stated in the form of Regional Regulations (Perda), so that the level of supervision and enforcement has certainty by the Kediri District Government. Second, to improve the limited quantity and quality of staff at the Licensing Service, it is necessary to add technical skills for staff related to technical licensing that require competency in accordance with licensing.